HANDWRITING EXPERTISE IN CIVIL CASES: COMPARATIVE ANALYSIS OF PROCEDURAL RULES - Beluga, Yuliia; Honcharuk, Olha (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: to study the regulatory framework for the use of handwriting expertise in civil proceedings within different legal systems and to determine its significance as a procedural means of proof. Research methods: document analysis and synthesis, comparative legal analysis, the method of objective truth, cognitive-analytical approach, among others. Results: generalized approaches to the appointment, conduct, and evaluation of handwriting expertise within civil proceedings; identified features of procedural regulation in Ukraine and selected foreign countries. Discussion: the legal nature of handwriting expertise was clarified, the role of the court and the expert in its appointment was defined; the principles of admissibility and relevance of evidence were analysed; the possibilities of harmonizing approaches to the use of expertise in civil cases were discussed; simplified procedures in certain jurisdictions were considered. In modern civil proceedings, which are based on the principles of adversarial proceedings, relevance and admissibility of evidence, forensic examination is of particular importance as a means of objectively establishing the facts of a case. Among the types of examinations most often appointed in cases concerning the invalidation of contracts, inheritance disputes, identification of document authorship, etc., handwriting examination occupies one of the leading places. It allows to confirm or refute the authenticity of a signature, to identify the person who made the handwritten note, which can be a decisive factor in establishing the truth. At the same time, the procedure for appointing, conducting and evaluating the results of handwriting analysis in civil proceedings is regulated by rules that have both common features in different jurisdictions and significant differences. This necessitates a comparative analysis of legal approaches to regulating the expert process in civil proceedings.